Implementation of Contextual Teaching and Learning (CTL) Strategies and Field Visit Techniques to Improve Student Learning Outcomes in Biotechnology Materials - Murni Desi; Suhendar Suhendar; Hidayati Herlina (Equator Science Journal, 2023)
This study aims to determine the effectiveness of the Contextual Teaching and Learning (CTL) learning model and Field Visit Techniques in Biotechnology learning for class IXC students of SMP Negeri 7 Sukabumi City in the 2022/2023, in terms of: (1) student learning motivation, (2) student learning outcomes in biotechnology learning by using Contextual Teaching and Learning (CTL) learning models and Field Visit Techniques. The research population was 25 class IXC students. The instruments used were student activity observation sheets and learning achievement tests. The data analysis technique uses a comparative descriptive analysis of test results between cycles with predetermined work indicators. The research results show that the effectiveness of the Contextual Teaching and Learning (CTL) learning model in science learning for class IXC students at SMP Negeri 7 Kota Sukabumi in the 2022/2023 academic year is effectively applied in learning. This research has obtained information regarding the effectiveness of the Contextual Teaching and Learning (CTL) learning model in biotechnology learning for students in IXC class, SMP Negeri 7 Sukabumi, in the 2022/2023 academic year.